2013
DOI: 10.1021/jp406540p
|View full text |Cite
|
Sign up to set email alerts
|

On the Size and Structure of Helium Snowballs Formed around Charged Atoms and Clusters of Noble Gases

Abstract: Helium nanodroplets doped with argon, krypton, or xenon are ionized by electrons and analyzed in a mass spectrometer. HenNgx+ ions containing up to seven noble gas (Ng) atoms and dozens of helium atoms are identified; the high resolution of the mass spectrometer combined with advanced data analysis make it possible to unscramble contributions from isotopologues that have the same nominal mass but different numbers of helium or Ng atoms, such as the magic He2084Kr2+ and the isobaric, nonmagic He4184Kr+. Anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 78 publications
12
77
1
Order By: Relevance
“…For example, the abundance distribution of ArHe + n which reveals three anomalies [50] is in striking agreement with computed dissociation energies [51]. Unfortunately, the only system for which energies of (C 60 ) m Cs z+ n have been computed versus a continuous range of n values, thus allowing the extraction of D n values, is C 60 Li z+ n with z = 0, 1, 2, and n 14 [3].…”
Section: Discussionsupporting
confidence: 64%
“…For example, the abundance distribution of ArHe + n which reveals three anomalies [50] is in striking agreement with computed dissociation energies [51]. Unfortunately, the only system for which energies of (C 60 ) m Cs z+ n have been computed versus a continuous range of n values, thus allowing the extraction of D n values, is C 60 Li z+ n with z = 0, 1, 2, and n 14 [3].…”
Section: Discussionsupporting
confidence: 64%
“…Bartl et al [25] have recently reported equivalent shells for He n Ar þ and draw an analogy between icosahedral He 12 Ar þ and C þ 60 , where the coating of the latter by helium leads to a rigid helium layer [28]. It is the corrugations on the C þ 60 surface that lead to a rigid helium layer, and the same applies to the helium coating of He 12 Ar þ .…”
Section: Prl 117 273001 (2016) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 98%
“…The smallest magic anion is consistent with an icosahedral arrangement of 12 H 2 molecules in the first shell around a central H − core. The larger magic cluster anions can also be interpreted in terms of icosahedral-like structures by analogy with cationic clusters between atomic ions and helium atoms [25]. Thus, the n ¼ 65 magic anion can be explained by a second shell of 20 H 2 molecules occupying the 20 triangular faces of a regular icosahedron, generating a dodecahedral arrangement.…”
mentioning
confidence: 99%
“…The notion of a solid snowball surrounding a positive ion embedded in liquid helium is very well established 11,17,19,22,23 . It has been suggested that increased pressure may cause structural transitions 46 .…”
Section: Structure Of the Atkins' Snowballsmentioning
confidence: 99%